Interpreting justice in the new student admission system: A Gadamerian hermeneutic analysis - Rita Diniati; Habib Rachman Sayekti (Jurnal Penelitian Ilmu Pendidikan, 2025)
This article examines how justice is articulated and negotiated in Indonesia’s the school admission selection system through a Gadamerian hermeneutic lens. Using qualitative hermeneutic analysis of policy documents and stakeholder perspectives, the study interprets how zoning, affirmative pathways, and merit-based selection shape understandings of distributive justice, recognition, and educational quality. The analysis shows that the school admission selection system reduces some overt forms of discrimination yet generates new grey zones, opportunities for document manipulation, and unequal school quality, so that formal equality of access does not ensure substantive justice. Justice in the school admission selection system emerges as a dynamic process in which meanings differ across social, economic, and cultural positions and must be continually renegotiated through dialogue. The article argues that policy makers and school communities need participatory, context sensitive implementation, combining equal access, recognition of diversity, and long-term improvement of school quality to realise more just admission practices. These insights inform future admission reforms.